ASSESSMENT OF THE DEVELOPMENT LEVEL AND PROBLEMS OF PROVIDING THE SOCIAL TAXI SERVICE FOR PEOPLE WITH LIMITED MOBILITY IN THE RUSSIAN FEDERATION REGIONS - Moskaleva, Natalia B.; Zaitseva, Natalia A.; Larionova, Anna A.; Dmitrieva, Nina V.; Breusova, Eugenia A.; Sharipova, Khadicha R.; Vikhrova, Natalia O. (International Journal of Psychosocial Rehabilitation, 2020)
Relevance of the research topic is determined by extremely limited study of functioning problems and "Social taxi" service development in the subjects of the Russian Federation, as well as full absence of research on this subject in the whole country. The aim of the study is to assess the development level of the Social Taxi service for low-mobility citizens in the regions of the Russian Federation, to substantiate problems that inhibit the development of this service in the Russian regions, as well as the justification of measures that can eliminate the identified problems or minimize them. When implementing the study, the authors of the article used the methods of quantitative and qualitative assessment, comparative and factor analysis, analysis and synthesis, grouping and comparison, while formulating conclusions based on the results of the study, the method of logical generalization. According to the results of complex analysis in each of the 85 subjects of the Russian Federation they assessed the condition services development in Russia on the basis of determining the percentage of citizens with limited mobility coverage by this service. The cost of the Social Taxi service in all constituent entities of the Russian Federation is analyzed. Data on the subjects of the Russian Federation with a high and minimum cost of services are summarized, measures are proposed for optimizing tariffs for the services of the Social Taxi. It is proposed that the development of the “Social Taxi” service should be given priority in the implementation of the state program “Accessible Environment”, which will ensure the development provided by this service in all regions of Russia. The authors determined the necessity to attract private investors and socially oriented non-profit organizations to Social Taxi service. Article submissions can be of interest to regional and federal authorities involved in the development of regional social programs, as well as scientists and experts engaged in the study of this subject.